IMPLICIT COMPARATIVE LAW - Macdonald, Roderick; Glover, Kate (Revue de droit de l'Université de Sherbrooke, 2013)
Contemporary comparative law scholarship has been enriched, methodologically and theoretically, by careful, searching accounts of the essence, aims and limits of the comparative legal endeavour. Yet, despite creative contributions to the field, most scholarly analyses remain tethered to conceptions of law demarcated by traditional boundaries – the official, the explicit and the external. In this paper, we contemplate what comparative law would look like if its practitioners abandoned their attachment to state legal positivism and adopted instead an approach grounded in a pluralist hypothesis of law. The alternative that we envision, which posits individuals rather than agents of official systems as the central legal (and comparative) actors. Moreover, it does not privilege explicit forms of normativity over the equally influential tacit forms that are inherent in all legal orders. Finally, this approach values the comparisons at stake in the everyday actions and interactions of individuals. Ultimately, we offer a response to the question: Whose comparisons, of what law, along which axes, by what method, to what end?